Global value chain participation impacts carbon emissions—Take the electro-optical equipment industry as an example - Ma, Xiaoming; Liu, Xin; Pan, Xiaoli; Liao, Xiawei (Frontiers in Environmental Science, 2022)
This study selects the electro-optical equipment manufacturing industry as an example to explore whether participation in Global Value Chain increases or mitigates a country’s carbon emissions and what are the impacting factors. Based on multi-regional input-output tables, a value-added decomposition model is used to decompose forward and backward value-added/final products of the world's electro-optical equipment manufacturing industries in 65 countries from 2005 to 2015. Impacts of several Global Value Chain participation characteristics, including position, forward participation and production length, backward participation and production length, on a country’s carbon emissions are examined. The results show that Asian countries have the highest participation rate in the global value chain, both forward and backward, of the electro-optical equipment sector with increasing proportions for forward participation, but lowest backward participation, in simple global value chains. Increase in forward Global Value Chain participation contributes to reducing carbon emission intensity of the electro-optical equipment manufacturing industry, particularly in terms of simple Global Value Chain participation. On the other hand, the production length of backward simple Global Value Chain is positively correlated with the total imported carbon emission intensity, indicating that the longer the simple Global Value Chain of foreign production is included in the industry’s imported intermediate products and the lower the country’s position in the Global Value Chain is, the higher its imported carbon emission intensity is. Upgrade in Global Value Chain is able to reduce the embodied carbon emissions in the intermediate product exports as well as total imports.